Diagnosis of sentinel lymph nodes in patients with cancer of the larynx and laryngopharynx using a new radiopharmaceutical based on technetium-99m-labeled gamma aluminum oxide - A. A. Medvedeva; V. I. Chernov; O. D. Bragina; R. V. Zeltchan; E. L. Choynzonov; S. Yu. Chizhevskaya; A. N. Rуbina; A. V. Gol’dberg; O. V. Сheremisina (Бюллетень сибирской медицины)
Аim. To study the possibility of using a radiopharmaceutical based on aluminum oxide labeled with 99mТс ([99mТс]-Al2O3) for the diagnosis of sentinel lymph nodes (SLN) in tumors of the larynx and laryngopharynx in comparison with a phytate colloid ([99mTc]-phytate colloid).Materials and methods. The study included patients with cancer of the larynx and laryngopharynx (T2–4N0M0) (n = 54). In the prospective group (n = 30), [99mТс]-Al2O3 was used as a radiopharmaceutical, in the retrospective group (n = 24), [99mТс]-phytate colloid was used. All radiopharmaceuticals were introduced endoscopically into the submucosal space along the periphery of the tumor. After 18 hours, single-photon emission computed tomography (SPECT) and intraoperative SLN detection were performed.Results. In the retrospective group, SLNs were detected in 20 out of 24 patients. A total of 32 lymph nodes were identified in the retrospective group. The median number of detected lymph nodes in one patient was 1.3 [0–3], the intensity of the radiopharmaceutical uptake on scintigrams was 2.2 [0.7–8.1], intraoperatively – 4 [1.6–9.0]. In the prospective group, [99mTc]-Al2O3 uptake in the lymph nodes of the neck was determined in 27 patients (90%); in3 patients, SLNs were not visualized. A total of 57 lymph nodes were identified (in 27 patients). The median number of visualized SLNs was 1.5 [0–5], the intensity of [99mТс]-Al2O3 uptake according to SPECT and intraoperative detection was 4.8 [0.7–19.4] and 6 [1.1–22.0], respectively.Conclusion. The most significant advantage of using [99mТс]-Al2O3 as a radiopharmaceutical is its high uptake in SLNs, which leads to an increase in the sensitivity of the method as a whole up to 90 versus 83% when using [99mTc]-phytate colloid.